The Epistemological Problem of Historical Causality in History Teaching: The role of Causes in the Explanations of Eight Social Studies Teachers - Meléndez Montero, Arturo (2023)
The objective of this article is to know how the epistemological problem of historical causality manifests itself in the teaching of history focusing especially on the historical explanations developed by teachers.  For this, first a theoretical-epistemological discussion is presented regarding the causes and their functioning in the historical explanation recognizing that the systemic approach supposes an overcoming of the reductionisms related to the nomological and intentional types of explanation.  Secondly, an empirical study carried out through a qualitative survey applied to eight Social Studies teachers is exposed.  It is concluded that most of these educators do not understand the complex nature of historical causality which is why they base their explanations on epistemological reductionisms.